Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.